Green synthesis, characterization of silver and zinc oxide nanoparticles using plant extract and evaluation of their biological activities - AZZI, Manel (Universty Of El-oued جامعة الوادي, 2024)
The primary aim of this study is to biosynthesize Ag/Ag2O NPs and ZnO NPs using Olea europaea var. Chemllali leaves aqueous extract. Additionally, the biological effects of these nanoparticles will be assessed both in vitro and in vivo. Qualitative, quantitative analysis and HPLC analysis was used for the identification of specific phenolic components of the extract. However, Ag/Ag2O NPs and ZnO NPs have been green synthesized and characterized using more then one technique (UV, FTIR, XRD, and SEM- EDX). Furthermore, antioxidant, antibacterial, antimutagenic, anticoagulant activities have been used to evaluate the in vitro activities. For in vivo study using Wistar male rats, to evaluate the extent of toxicity of these nanoparticles, and to assess protective effect of this nanoparticles against metrubizin toxicity. Some biochemical and hematological indicators, also histopathological and oxidative stress parameter of liver, kidney and spleen were mesured. Phytochemical analysis revealed the presence of many seconder metabolites in aquous extract, also quantified of the total phenolic, flavonoids and condensed tanins content. Additional analyze by HPLC,we have identified eight phenolic compounds; when quercetin (1945.90 μg/g) was the most abundant element. After characterization of biogenic nanopartilces, we confirmed that Ag/Ag2O NPs and ZnO NPs were biosynthesized. The average size distribution of Ag/Ag2O NPs is principally 45 nm, and 18.79 nm for ZnO NPs size. For antioxidant activities of the O.europaea leaf extract, Ag/Ag2O NPs and ZnO Nps is shown to be dose-dependent, as the scavenging activity, TAC and FRAP, the most notable antioxydant activities were observed with 200 μg/mL of Ag/Ag2O Nps. The antibacterial activity in solid agar was found also to be dose-dependent of Ag/Ag2O NPs against S.aureus, E.coli, and P. aeruginosa, while the ZnO nanoparticles at higher dose was less effective. However, antibacterial kinetic study in liquid medium revealed inhibitory effects of nanoparticles on bacterial growth of E. coli and S. typhimurium cells at 200ug/ml, but the growth of B. cereus and MS-S. aureus cells was suppressed in the initial hours, with almost all bacterial cells exhibiting retarded growth after this period. This tow nanoparticles biosynthetised showed strong anti-mutagenicity against S. typhimurium TA98, when the percent inhibition of ZnO NPs was stronger (76.24%) then Ag/Ag2O NPS (70%) at 250 μg/plat. All nanoparticles (ZnO and Ag/Ag2O NPs) prevented coagulation similarly to the positive control (EDTA). Toxicity study of nanoparticles revealed no mortality for ZnO NPs (50 mg/kg and 100 mg/kg b.w) and Ag/Ag2O NPs (2.5 mg/Kg) for single dose during the 28-days. In contrast, one rat that received a higher dose of 5 mg/kg b.w of Ag/Ag2O NPs died after 24 h, and we showed signs of toxicity in this group. Moreover, the findings in metribuzin-treated rats induced for 21 days significant changes in hematological, biochemical parameters and imbalance in oxidative stress status and deterioration of the liver, the kidney and the spleen structure compared to the control group. However, the treatment with ZnO NPs (2.5 mg/Kg , 5 mg/Kg) mitigated most of toxic effects and the restored most of previous parameters. As for Ag/Ag2O NPs, most of the effects of low concentration (0.062mg/Kg) were generally beneficial. On the other hand, the effect of high concentration (0.125mg/Kg) was hopeless and even toxic, as demonstrated by the analyzes and histological images of the organs studied. En conclusion, this work realizes the potential for green synthesis of nanoparticles from O. europaea (ZnO NPs and Ag/Ag2O NPs), as these particles have shown to be highly biological efficient and varied among them, While Ag/Ag2O NPs was toxic to a certain degree.إليك ترجمة للنص الذي قدمته: --- ## ترجمة الدراسة الهدف الرئيسي من هذه الدراسة هو التخليق الحيوي لجسيمات Ag/Ag2O النانوية وجسيمات ZnO النانوية باستخدام مستخلص مائي من أوراق *Olea europaea* var. Chemllali. بالإضافة إلى ذلك، سيتم تقييم التأثيرات البيولوجية لهذه الجسيمات النانوية في كل من الدراسات في المختبر (in vitro) وفي الجسم الحي (in vivo). تم استخدام التحليل النوعي والكمّي وتحليل HPLC لتحديد المكونات الفينولية المحددة في المستخلص. تم تخليق جسيمات Ag/Ag2O النانوية وجسيمات ZnO النانوية بطريقة خضراء وتمت معرفتها باستخدام أكثر من تقنية (UV، FTIR، XRD، وSEM-EDX). علاوة على ذلك، تم استخدام الأنشطة المضادة للأكسدة والمضادة للبكتيريا والمُضادة للطفرات والمُضادة للتخثر لتقييم النشاطات في المختبر. لإجراء الدراسة في الجسم الحي، تم استخدام جرذان ويستار الذكور لتقييم مدى سمّية هذه الجسيمات النانوية، وكذلك لتقييم أثرها الوقائي ضد سمّية المادة المتروبيزين. تم قياس بعض المؤشرات البيوكيميائية والدموية، بالإضافة إلى معايير الإجهاد التأكسدي والهيستوباثولوجيا للكبد والكلى والطحال. كشفت التحليلات الفيتوكيميائية عن وجود العديد من المُركبات الثانوية في المستخلص المائي، كما تم تحديد كمية الفينولات الإجمالية والفلونويدات والتانينات المكثفة. من خلال التحليل الإضافي بواسطة HPLC، تم تحديد ثمانية مركبات فينولية، حيث كانت الكيرسيتين (1945.90 µg/g) العنصر الأكثر وفرة. بعد تحديد الجسيمات النانوية البيولوجية، تأكدنا من أن جسيمات Ag/Ag2O وZnO قد تم تصنيعها حيوياً. كان متوسط توزيع حجم جسيمات Ag/Ag2O حوالي 45 نانومتر، و18.79 نانومتر لجسيمات ZnO. أما بالنسبة للنشاطات المضادة للأكسدة لمستخلص أوراق *O. europaea*، فقد أظهرت جسيمات Ag/Ag2O وZnO نتائج تعتمد على الجرعة، حيث لوحظت الأنشطة المضادة للأكسدة الأكثر وضوحًا عند 200 µg/mL من جسيمات Ag/Ag2O. كما وجد أن النشاط المضاد للبكتيريا في وسط الآغار الصلب يعتمد أيضًا على الجرعة لجسيمات Ag/Ag2O ضد *S. aureus* و*E. coli* و*P. aeruginosa*، في حين كانت فعالية جسيمات ZnO أقل عند الجرعات الأعلى. مع ذلك، كشف دراسة ديناميكية النشاط المضاد للبكتيريا في الوسط السائل عن تأثيرات مثبطة للجسيمات النانوية على نمو البكتيريا مثل *E. coli* و*S. typhimurium* عند 200 µg/mL، لكن نمو *B. cereus* و*MS-S. aureus* قد تم قمعه في الساعات الأولية، مع تأخر في نمو جميع الخلايا البكتيرية تقريبًا بعد هذه الفترة. أظهرت هاتان الجسيمتان النانوية المُصنّعتان حيوياً فعالية قوية ضد الطفرات فيما يتعلق بـ*S. typhimurium TA98*، حيث كانت نسبة تثبيط جسيمات ZnO أعلى (76.24%) من جسيمات Ag/Ag2O (70%) عند 250 µg/طبق. جميع الجسيمات النانوية (ZnO وAg/Ag2O) منعت التخثر بشكل مشابه للتحكم الإيجابي (EDTA). كشفت دراسة السُمّية للجسيمات النانوية عن عدم وجود وفيات لجسيمات ZnO (50 ملغ/كغ و100 ملغ/كغ وزن حي) وجسيمات Ag/Ag2O (2.5 ملغ/كغ) عند إعطائها جرعة واحدة خلال 28 يومًا. على النقيض من ذلك، توفي جرذ واحد تلقى جرعة أعلى من 5 ملغ/كغ وزن حي من جسيمات Ag/Ag2O بعد 24 ساعة، وظهرت علامات السُمّية في هذه المجموعة. علاوة على ذلك، أحدثت النتائج في الجرذان المعالجة بالمتروبيزين على مدار 21 يومًا تغييرات ملحوظة في المعايير الدموية والبيوكيميائية وعدم توازن في حالة الإجهاد التأكسدي وتدهور في هيكل الكبد والكلى والطحال مقارنة بمجموعة التحكم. ومع ذلك، خفف العلاج بجسيمات ZnO (2.5 ملغ
في العلوم الطبيعة و الحياةApplied Biochemistryأطروحة دكتوراه تخصص
Keywords: biosynthesize . O.europaea; ZnO NPs; Ag/Ag2O NPs; antibacterial; antimutagenic; toxicity; التخليق الحيوي لجسيمات أكسيد الزنك (ZnO NPs) وجسيمات الفضة/أكسيد الفضة (Ag/Ag2O NPs) باستخدام